2006
DOI: 10.1038/nature04336
|View full text |Cite
|
Sign up to set email alerts
|

Tunicates and not cephalochordates are the closest living relatives of vertebrates

Abstract: Tunicates or urochordates (appendicularians, salps and sea squirts), cephalochordates (lancelets) and vertebrates (including lamprey and hagfish) constitute the three extant groups of chordate animals. Traditionally, cephalochordates are considered as the closest living relatives of vertebrates, with tunicates representing the earliest chordate lineage. This view is mainly justified by overall morphological similarities and an apparently increased complexity in cephalochordates and vertebrates relative to tuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

47
1,024
3
17

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,496 publications
(1,091 citation statements)
references
References 34 publications
47
1,024
3
17
Order By: Relevance
“…Ces résultats mettent en perspective d'autres observations similaires rapportées récemment au cours de l'étude de modèles murins d'inactivation du facteur PTEN [5,6], situé en amont de FoxO dans la voie PI3K/AKT, et du facteur de transcription ATM (ataxia telangiectasia mutated) [7]. Bien qu'aucun lien entre FoxO et ATM n'ait été décrit à ce jour, l'expression d'ATM et d'une de ses cibles, p16 INK4a , est modifiée dans les souris FoxO1/3/4 -/-.…”
Section: Perspectivesunclassified
See 1 more Smart Citation
“…Ces résultats mettent en perspective d'autres observations similaires rapportées récemment au cours de l'étude de modèles murins d'inactivation du facteur PTEN [5,6], situé en amont de FoxO dans la voie PI3K/AKT, et du facteur de transcription ATM (ataxia telangiectasia mutated) [7]. Bien qu'aucun lien entre FoxO et ATM n'ait été décrit à ce jour, l'expression d'ATM et d'une de ses cibles, p16 INK4a , est modifiée dans les souris FoxO1/3/4 -/-.…”
Section: Perspectivesunclassified
“…La complexité de la fonction des facteurs FoxO et l'importance du contexte cellulaire sont également mises en évidence par l'augmentation de l'apoptose des progéni-teurs myéloïdes en l'absence de différence du taux de ROS, une observation qui reste inexpliquée dans ce modèle. Les (Figure 1) [5]. Ce changement de notre vision de la phylogénie des chordés est très important dans notre compréhension du caractère ancestral ou non des différents aspects du déve-loppement embryonnaire chez les chordés.…”
Section: Perspectivesunclassified
“…Genomic approaches to chordate phylogenies suggested changes to the traditional euchordate view-vertebrates and cephalochordates as sister groups to the exclusion of basal tunicates-and placed vertebrates and tunicates as sister groups (the Olfactores hypothesis) (Blair and Hedges, 2005;Delsuc et al, 2006;Philippe et al, 2005). These novel ideas have been subjected to thorough testing and the Olfactores hypothesis has received further support (Bourlat et al, 2006;Delsuc et al, 2006Delsuc et al, , 2008Dunn et al, 2008;Swalla and Smith, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These novel ideas have been subjected to thorough testing and the Olfactores hypothesis has received further support (Bourlat et al, 2006;Delsuc et al, 2006Delsuc et al, , 2008Dunn et al, 2008;Swalla and Smith, 2008). In contrast, the unorthodox assembly of cephalochordates and echinoderms, which initially raised suspicions about chordate monophyly (Delsuc et al, 2006), was not confirmed (Bourlat et al, 2006;Delsuc et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Cette question est d'autant plus importante que la fonction d'étanchéité assurée par les épithéliums découle directement de leur organisation polygonale. En tant que membre du groupe actuel le plus proche des vertébrés [6,7], Ciona intestinalis ( Figure 1A) a émergé comme un modèle de choix pour l'étude du développement embryonnaire. Cette espèce est facilement manipulable au laboratoire, son lignage cellulaire est connu, l'embryogenèse est rapide ( …”
unclassified